Establishing a church library for the Metro Manila Christian Church Quezon City sector - Ricafort, Patricia Ellis G.; Pascua, Sonia M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2014)
The Metro Manila Christian Church (MMCC) is a non-denominational Christian group based in the National Capital Region of the Philippines. The Quezon City Sector (QC Sector) with a membership of around 350 individuals, not including teens and children who are not officially part of the roster, is one of its largest groups by geographical subdivision. Its continuous growth in membership is a contribution to the developing market of religious, spiritual, and inspirational literature. Recognizing the needs of members for an organized collection of religious, spiritual, and inspirational literature, this study sought to determine the requirements for establishing a church library for the MMCC QC Sector.
A total of 38 teens and preteens and 154 adults answered the survey questionnaire personally administered by the researcher on March 2, 2014.
The data gathered from the official roster of the church and the survey questionnaires revealed that: (a) members were mostly below the age of 45; (b) there were twice as many female members as there were male members; (c) most members of the church achieved a higher education, were literate, and were employed; (d) English was the more preferred language; (e) 1/3 of the congregation belong to the Marrieds Ministry and another 1/3 of the congregation belong to the Singles Ministry; (f) most respondents were interested in reading and some respondents were not interested in reading but read every day; and (g) members were willing and able to help the establishment of the church library by donating in cash or in kind, etc.
The church library should contain 1000 volumes of books, mostly on the following topics: Bibles in various versions, books on Christian living and prayer, biblical reference books, books on families and parenting, books on love, courtship, and marriage, and books on theological topics or world religions. The church library should also have teaching aids, periodicals, and audiovisual materials. The collection should be classified according to a few categories and then arranged alphabetically according to the author's surname.
Users may borrow regular circulation books for one month but reserve books, references, and periodicals are for room use only. The church library should be open 30 to 60 minutes before and after Sunday worship and 15 to 30 minutes before and after Midweek Devotionals. To accommodate students and children, the church library should also be open during Saturdays. It may also remain open upon advance notice on Sunday afternoons after the Sunday Worship.
The church library as a space will be useful for social purposes, education and instruction especially to the children, and for studying the bible with visitors. It should provide an atmosphere that encourages productivity.
The startup cost for the library is PHP58, 142.40. Its operating cost in five years would sum up to PHP168,798.80
The main source of funding for the church library is the budget of the church. The church library should also come up with fund raising activities and clearly identified fines and fees would also aid and supplement the funds of the church library.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Church libraries -- Philippines -- Quezon City